Habitação como mercadoria: urbanização, financeirização, e reificação da moradia em Palmas (TO) - Bazzoli, Rodrigo de Sousa (Universidade Federal do Tocantins, 2019)
The work presents the production of housing as a commodity, in the form of real estate product. Analyzing the aspects of the development of the house and cities, adopting as narrative, its subordination to the constitution of social relations of production, given by the use of the labor theory of value. The implications of the capitalist mode of production laid the foundations of the contemporary urban environment, shaping labor and consumption relations, and influencing social and everyday relations. It was defined research structuring based on three main points: urbanization, induced by the resignification of the values of land use; the financialization, brought about by the resignification of exchange values; and reification, which is manifested by the resignification of the 'sign' values of social and work relations, in this case, in the urban space and in the creation of housing lots. The concepts used in the formation of the theoretical bases of the text are transported to the observation in Palmas (TO), the implications of this process (social, economic and under urban morphology) are presented through conclusive discussions, presenting the mechanisms of appropriation and the cycles of accumulation of land capital in the formation of the capital of Tocantins.